Are family members expropriated-monitoring shareholders? non-linear evidence from the Saudi Arabia - Shehabaddin Abdullah A. Al-Dubai; Ku Nor Izah Ku Ismail; Noor Afza Amran (Penerbit Universiti Kebangsaan Malaysia, 2015)
As family businesses grow worldwide, the significant role of family shareholders on firm value becomes questionable. This study seeks to address this issue and provides new evidence on the non-linearity of family ownership-firm value relationship, based on 375 firm-year observations of 75 public listed companies in Saudi Arabia over five consecutive years (2007- 2011). Interestingly, we provided evidence that the behavior of the Saudi families is changeable between expropriation and monitoring during the life of the business depending on the percentage of family ownership. We found sufficient evidence that the turning point occurs at the 28% family ownership. This confirmed the expropriated-monitoring behavior of family shareholders in their businesses. These results were robust with respect to different family definitions and analyses. Our findings suggested that investors should not undervalue Saudi family firms due to family ownership per se. At a certain degree of ownership, the benefits of Saudi family monitoring actually exceed the costs. The results suggested that there may be a need to encourage policy makers in Saudi Arabia to impose the full disclosure of firms’ ownership information, including the percentage of ownership and the identity of owners.